PENGARUH FITUR (FEATURES) DAN TARIF (FARE) TERHADAP LOYALITAS PELANGGAN KARTU INDOSAT PADA MAHASISWA ADMINISTRASI BISNIS ANGKATAN 2009 REGULER 1 DAN REGULER 2 FAKULTAS ILMU SOSIAL DAN ILMU POLITIK UNIVERSITAS DIPONEGORO - Jatmiko, Ibnu; Lubis, Nawazirul; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2013)
Consumers loyalty affected by many factors, between features and fare. Based on problem in this research is decline of Indosat costumers amount at 2009 as much as 3,4 million costumers and Indosat’s strongest competiters not experiencing this. This research purpose to find out whether have influences between features and fare on consumers loyalty.This research used explanatory research type. Take 77 respondents as sample by saturated sample. Collecting data used questionnaire. Hypotheses tested by correlation coefficient, determination coefficient, t test, and F test.Result this research show that features have positive influence and significant on consumers loyalty. Fare have positive influence and significant on consumers loyalty. Features and fare simultaneous have positive influences and significant on consumers loyalty.For headmaster of Indosat proposed to develop features on Indosat’s provider and establish affordable fare to keep consumers loyalty. Developing of features and establishing affordable fare be able to compete with the other provider. For next research need to research about factors be sides features and fare influences on consumers loyalty.